Enlarging the process window in absorber-free laser transmission welding of polymer foils using tailored laser intensity distribution - Maiwald, Frederik; Kroth, Lea; Laskin, Alexander; Hierl, Stefan; Schmidt, Michael (Procedia CIRP, 2024)
Absorber-free laser transmission welding enables precise and clean joining of polymer foils without absorbent additives or adhesives. It is well suited for applications in medical technology and food industry, which impose high demands on process reliability. To achieve a large process window and thus a reliable process, a homogeneous weld seam temperature is desirable. For this purpose, the intensity distribution of the laser beam is adapted locally by refractive beam shaping optics. Using a donut-shaped intensity distribution, the weld seam temperature is homogenized. Thus, the process window for welding polypropylene or polyethylene foils is enlarged up to a factor of 4 compared to a conventional, Gaussian-shaped distribution. This enables the reliable welding of even 85 μm thin foils, which could only be welded to a limited extent with a conventional laser intensity distribution.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Beam shaping; Foils; Laser welding; Polymer